Comparing Patient-Reported Outcomes in Patients Undergoing Lumbar Fusion for Isthmic Spondylolisthesis with Predominant Back Pain versus Predominant Leg Pain Symptoms - Jacob, Kevin C.; Patel, Madhav R.; Vanjani, Nisheka N.; Pawlowski, Hanna; Prabhu, Michael C.; Singh, Kern (World neurosurgery, 2022)
To compare patient-reported outcome measures (PROMs) and minimum clinically important difference (MCID) achievement following anterior or transforaminal lumbar interbody fusion for isthmic spondylolisthesis in patients presenting with predominant back pain versus predominant leg pain symptoms. A single-surgeon database was reviewed for anterior or transforaminal lumbar interbody fusion procedures for isthmic spondylolisthesis. Patient demographics, perioperative characteristics, postoperative complications, and PROMs were collected. Demographic/perioperative characteristics were compared among groups using χ2 and Student t tests for categorical and continuous variables, respectively. Mean PROM scores were compared using an unpaired Student t test. Postoperative improvement from preoperative baseline within each cohort was assessed with paired-samples t test. MCID achievement rates were compared with χ2 analysis. In total, 143 patients were included with 65 patients in the predominant back pain and 78 patients in the predominant leg pain cohort. Preoperative visual analog scale (VAS) leg was noted to be significantly greater in predominant leg pain cohort (P < 0.001). Cohorts demonstrated significant mean postoperative differences for the following PROMs at the following postoperative time points: significant differences were noted between cohorts for rate of achievement of MCID for the following PROMs at the following time points: VAS back at 2 years and VAS leg at 6 weeks/12 weeks/6 months/overall (P < 0.036, all). Compared with patients presenting for surgery with predominant leg pain symptoms, patients undergoing lumbar fusion at L4–L5 and L5–S1 for isthmic spondylolisthesis with predominant back pain symptoms may demonstrate improved long-term clinical outcomes for reported back pain, leg pain, and disability and reduced postoperative length of stay and narcotic consumption.